2022
DOI: 10.1080/22221751.2022.2140611
|View full text |Cite
|
Sign up to set email alerts
|

Shared IGHV1-69-encoded neutralizing antibodies contribute to the emergence of L452R substitution in SARS-CoV-2 variants

Abstract: SARS-CoV-2 variants continue to emerge facing established herd immunity. L452R, previously featured in the Delta variant, quickly emerged in Omicron subvariants, including BA.4/BA.5, implying a continued selection pressure on this residue. The underlying links between spike mutations and their selective pressures remain incompletely understood. Here, by analyzing 221 structurally characterized antibodies, we found that IGHV1-69-encoded antibodies preferentially contact L452 using germline-encoded hydrophobic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…7). In particular, we note that the VH1-69 "HCDR2 epitope", a hydrophobic patch in RBD formed by L452, F490 and L492 previously noted by us 10,36 , is contacted by SHM introduced "up" RBD "up" RBD "up" RBD "down" RBD "down" RBD "down" RBD "down" RBD "down" RBD "down" RBD "down" RBD "down" RBD "down" RBD "up" RBD "up" RBD "up" RBD "up" RBD "up" RBD "up" RBD "up" RBD "up" RBD "up" RBD S30G S30G S30G S30I of HCDR1, 55I ins and 56L ins of HCDR2 (Fig. 4b).…”
Section: A Highly Unusual Hcdr2 Insertion Is Essential For Crossneutr...mentioning
confidence: 50%
See 3 more Smart Citations
“…7). In particular, we note that the VH1-69 "HCDR2 epitope", a hydrophobic patch in RBD formed by L452, F490 and L492 previously noted by us 10,36 , is contacted by SHM introduced "up" RBD "up" RBD "up" RBD "down" RBD "down" RBD "down" RBD "down" RBD "down" RBD "down" RBD "down" RBD "down" RBD "down" RBD "up" RBD "up" RBD "up" RBD "up" RBD "up" RBD "up" RBD "up" RBD "up" RBD "up" RBD S30G S30G S30G S30I of HCDR1, 55I ins and 56L ins of HCDR2 (Fig. 4b).…”
Section: A Highly Unusual Hcdr2 Insertion Is Essential For Crossneutr...mentioning
confidence: 50%
“…Among these, Sheward et al reported a VH3-53 antibody with different CDRs from YB9-258 likely to withstand Omicron variants by a different molecular mechanism 54 . It has been reported that Omicron BA.1 resistant VH3-53/ VH3-66 and VH1-69 antibodies are recalled in Omicron BA.1 breakthrough infections 12,16,36 . Isolation of Omicron resistant VH3-53 and related VH3-66 antibodies YB12-197 and YB9-258 in this study shown in colors and 47D1 is shown in gray.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the top highly expressed genes, we found some small nuclear and long noncoding RNAs such as RN7SKP255, RN7SK, that are known to play a role in macrophage differentiation, polarization, and innate immune functions [32, 33]. IGHV1-69-2 gene encoding the Immunoglobulin heavy variable was also found among the top expressed genes alongside H2BP2, an extrachromosomal histone that stimulates innate and acquired immune defenses in different cells upon detection of double-stranded DNA (dsDNA) fragments derived from infectious agents or damaged cells [34, 35].…”
Section: Resultsmentioning
confidence: 99%